Nutrient structure dynamics and microbial communities at the water–sediment interface in an extremely acidic lake in northern Patagonia - Cuevas, Mayra; Francisco, Issotta; Díaz-González, Fernando; Diaz, Mónica; Quatrini, Raquel; Beamud, Guadalupe; Pedrozo, Fernando; Temporetti, Pedro (Frontiers in Microbiology, 2024)
Lake Caviahue (37º 50 'S and 71º 06' W; Patagonia, Argentina) is an extreme case of a glacial, naturally acidic, aquatic environment (pH ~ 3). Knowledge of the bacterial communities in the water column of this lake, is incipient, with a basal quantification of the bacterioplankton abundance distribution in the North and South Basins of Lake Caviahue, and the described the presence of sulfur and iron oxidizing bacteria in the lake sediments. The role that bacterioplankton plays in nutrient utilization and recycling in this environment, especially in the phosphorus cycle, has not been studied.In this work, we explore this aspect in further depth by assessing the diversity of pelagic, littoral and sediment bacteria, using state of the art molecular methods and identifying the differences and commonalties in the composition of the cognate communities. Also, we investigate the interactions between the sediments of Lake Caviahue and the microbial communities present in both sediments, pore water and the water column, to comprehend the ecological relationships driving nutrient structure and fluxes, with a special focus on carbon, nitrogen, and phosphorus. Two major environmental patterns were observed: a) one distinguishing the surface water samples due to temperature, Fe 2+ , and electrical conductivity, and b) another distinguishing winter and summer samples due to the high pH and increasing concentrations of N-NH4 + , DOC and SO4 2-, from autumn and spring samples with high soluble reactive phosphorus (SRP) and iron concentrations. The largest bacterial abundance was found in autumn, alongside higher levels of dissolved phosphorus, iron forms, and increased conductivity. The highest values of bacterial biomass were found in the bottom strata of the lake, which is also where the greatest diversity in microbial communities was found. The experiments using continuous flow column microcosms showed that microbial growth over time, in both the test and control columns, was accompanied by a decrease in the concentration of dissolved nutrients (SRP and N-NH4 + ), providing proof that sediment microorganisms are active and contribute significantly to nutrient utilization/mobilization.